Establishing Stronger Connections: Enhancing School-Family Collaboration for Students with Hearing Impairments - Jeremy S. Sates (Future Science / FSH-PH Publications, 2026)
This study sought to investigate approaches that improve school-family partnerships in supporting hearing-impaired learners in selected Special Education (SPED) centers in Cebu. This study utilized a comparative descriptive design and sought to find out the similarities and differences between teachers and parents on aspects of communication approaches and shared decision-making in the learning process of hearing-impaired learners. The respondents of this study were SPED center teachers and parents of hearing-impaired learners chosen through purposive sampling. The total number of respondents was 50. The researcher used a validated survey questionnaire to gather data. This data was then analyzed using descriptive statistics and t-tests to find differences between and within the groups of people surveyed. The findings of this study revealed that hearing-impaired learners benefit from improved communication approaches and parental involvement in addressing issues affecting academic performance and boosting students’ self-esteem and social behavior. This study therefore concludes that school-family partnerships are vital in the development of hearing-impaired learners and suggests that parent training and community support are vital in addressing issues affecting hearing-impaired learners in Cebu.